Povezanost med mladostnikovimi odnosi s starši in vrstniki ter uživanjem zdravju škodljivih substanc - Cugmas, Zlatka (Psihološka obzorja (Ljubljana), 2010)
The aim of the study was to investigate the correlations between adolescents' perception of their relationship with mother, father and peers, parental monitoring, parental and peer influence, and frequency of substance use in the life and in the past month. 151 college students (43,7 % male) aged 18-22 years participated in the study. The results showed statistically significant negative correlations between frequency of substance use and adolescents' perception of: (1) open communication and (2) trust in their relationship with mother, father and peers, (3) parental monitoring, and (4) mother's influence. The correlations between frequency of substance use and adolescents' perception of (1) alienation from parents and peer, and (2) influence of peer were positive.
Keywords: attachment theory; navezanost; družinski odnosi; medosebni odnosi; mladostniki; vrstniki; starši; droge